2005
DOI: 10.1108/09555340510576230
|View full text |Cite
|
Sign up to set email alerts
|

A paradox of service quality in Turkey

Abstract: Purpose -Are there cases or contexts where certain groups of customers who are expected to place a considerable emphasis and importance on the tangible qualities of services end up attributing a greater weight to the intangible qualities? This paper attempts to exemplify the existence of such cases, and explain why such cases are, at times, paradoxical in nature, and how such cases could arise. Design/methodology/approach -The paper employs a structural-equation-modeling approach to theorize about, and empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…A comparison of the healthcare dimensions identified with those evident in the marketing literature indicates a considerable overlap, that is, both literatures identify the importance of the technical, functional, environment, administrative and personnel dimensions of the service experience. The application of SERVQUAL in health service quality analysis showed that intangible elements tend to be more influential than tangible ones (Kara, Lonial, Tarim, & Zaim, 2005), although one should always consider adapting the scale in specific situations. It is noticeable that the majority of studies about service quality in healthcare do not provide a comprehensive outcome element, which could be due to difficulties in measuring the results in healthcare service quality.…”
Section: Health Care Service Quality Measurementmentioning
confidence: 99%
“…A comparison of the healthcare dimensions identified with those evident in the marketing literature indicates a considerable overlap, that is, both literatures identify the importance of the technical, functional, environment, administrative and personnel dimensions of the service experience. The application of SERVQUAL in health service quality analysis showed that intangible elements tend to be more influential than tangible ones (Kara, Lonial, Tarim, & Zaim, 2005), although one should always consider adapting the scale in specific situations. It is noticeable that the majority of studies about service quality in healthcare do not provide a comprehensive outcome element, which could be due to difficulties in measuring the results in healthcare service quality.…”
Section: Health Care Service Quality Measurementmentioning
confidence: 99%
“…As a result, we extracted 32 items from literature study and made adjustment for the health examination service context. We utilized results of [29], [36], and [55] as major references. Since the health examination service provider of our choice offers service with no charge, items regarding cost ( [22], [29], [36], [54], [59]) have been removed.…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…Also, since consumers of health examination service are treated as outpatients, the items pertinent to inpatients have been excluded. These include discharge process [19], [36] and meal ( [19], [36], [55]). The finalized items and their references are depicted in Table V Review of measurement items was based on the pre-test and responses from professionals.…”
Section: Research Design and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…While Kara, Lonial, Tarim, and Zaim (2005) stated that intangible factors turn out to be among the most decisive ones in determining the service quality.…”
Section: Discussionmentioning
confidence: 99%